Dispersion-Solvent Control of Ionomer Aggregation in a Polymer Electrolyte Membrane Fuel Cell - Ji Hye Lee (Nature Portfolio, 2018)
Abstract In this study, we examined the influence of the dispersion solvent in three dipropylene-glycol/water (DPG/water) mixtures, with DPG contents of 0, 50, and 100 wt%, on ionomer morphology and distribution, using dynamic light scattering (DLS) and molecular-dynamics (MD) simulation techniques. The DLS results reveal that Nafion-ionomer aggregation increases with decreasing DPG content of the solvent. Increasing the proportion of water in the solvent also led to a gradual decrease in the radius of gyration (Rg) of the Nafion ionomer due to its strong backbone hydrophobicity. Correspondingly, MD simulations predict Nafion-ionomer solvation energies of −147 ± 9 kcal/mol in water, −216 ± 21 kcal/mol in the DPG/water mixture, and −444 ± 9 kcal/mol in DPG. These results suggest that higher water contents in mixed DPG/water solvents result in increased Nafion-ionomer aggregation and the subsequent deterioration of its uniform dispersion in the solvent. Moreover, radial distribution functions (RDFs) reveal that the (-CF2CF2-) backbones of the Nafion ionomer are primarily enclosed by DPG molecules, whereas the sulfonate groups (SO3 −) of its side chains mostly interact with water molecules.